Molecular recognition by the transcriptional activator AP 1 - Campbell, Kathleen M., author; Lumb, Kevin, advisor; Laybourn, Paul, committee member; Rithner, Christopher, committee member; Stargell, Laurie, committee member; Woody, Robert W., committee member (Colorado State University. Libraries, 2002)
Members of the Jun family of mitogen-inducible transcriptional activators homodimerize or heterodimerize with the Fos or ATF/CREB activators to form the transcriptional regulator AP-1. AP-1 activates transcription of genes involved in a diverse range of biological processes, including cell proliferation, differentiation, neuronal development, and apoptosis. This thesis addresses the structural and biochemical basis of AP-1 function. Fos and Jun heterodimerize, and Jun homodimerizes, via the leucine zipper coiled coil. Fos does not form a stable homodimer due to unfavorable interhelical electrostatic interactions in the Fos homodimeric coiled coil. Fos contains two lysine residues at positions that are buried in a dimeric coiled coil. Sedimentation equilibrium, circular dichroism and fluorescence indicate that substitution of one of these lysine residues with norleucine results in a very stable homotetramer with native-like properties, indicating that the electrostatic mechanism of Fos destabilization can be overcome by an oligomerization switch that is mediated by a buried polar residue. This finding was extended to protein design and used to impart dimerization specificity and native-like properties in a designed heterodimeric coiled coil. c-Fos contains a C-terminal activation domain that binds TBP (TATA-Binding Protein). Using a combination of circular dichroism, nuclear magnetic resonance, and hydrodynamic techniques, the C-terminal activation domain of human c-Fos was shown to be functional for transcriptional activation yet unfolded. Studies of the complex formed between C-terminal activation domain of Fos and TBP were hindered by the limited solubility of TBP. However, using analytical ultracentrifugation and immunoprecipitation techniques, TBP was shown to be predominately monomeric at physiological concentrations. This finding challenges the notion that DNA binding by TBP is regulated by TBP dimerization. c-Jun contains an N-terminal activation domain, which was also shown to be largely unfolded. Circular dichroism suggests that the Jun activation domain undergoes a folding transition upon binding the KIX domain of CBP (CREB-Binding Protein). A combination of circular dichroism and NMR reveals a novel mode of recognition of the KIX domain by c-Jun, and suggests a structural basis for combinatorial recruitment of CBP by multiple transcriptional activators.
Keywords: biochemistry